2002
DOI: 10.1159/000065473
|View full text |Cite
|
Sign up to set email alerts
|

Early Tandem High-Dose Ifosfamide, Carboplatin, Etoposide Therapy with Stem Cell Rescue for Small-Cell Lung Cancer: Brief Report on the Results of a Phase-I/II Trial

Abstract: Objective: High-dose therapy (HDT) for small-cell lung cancer is experimental. Late intensification HDT for chemosensitive disease can increase the number and quality of remissions and prolong relapse-free survival, but has not yet shown impact on overall survival. This is possibly due to resistant residual disease. To overcome the development of resistance, we have tested early intensification tandem HDT. Methods: We performed a phase-I/II trial using 1 conventional cycle of ifosfamide, carboplatin, etoposide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…28 -31 Multiple studies suggested that single or sequential reinfusion of PBPCs was feasible, allowing for the dose intensification of ICE by a factor of 1.80. [32][33][34][35][36][37][38][39][40][41] These studies reported significant improvements for patients with limited-disease SCLC but showed less benefit for patients with extensive-disease SCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 -31 Multiple studies suggested that single or sequential reinfusion of PBPCs was feasible, allowing for the dose intensification of ICE by a factor of 1.80. [32][33][34][35][36][37][38][39][40][41] These studies reported significant improvements for patients with limited-disease SCLC but showed less benefit for patients with extensive-disease SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in our study for ICT, only the concurrent use of hematopoietic growth factors with reinfusion of autologous hematopoietic progenitor cells allowed for more significant increases in dose intensity, which translated into increased response, prolonged time to relapse, and significantly increased survival. [32][33][34][35][36][37][38][39][40] Dose intensification is an attractive option for increasing the efficacy of treatments for SCLC. Earlier studies using the ICE regimen reported promising results, but their designs provided only limited information about actual survival benefit.…”
Section: Discussionmentioning
confidence: 99%